An Analysis on 2015 Village-Based English Training Program of Banyuwangi Regency - Irama, Zesy (LUNAR, 2017)
Tourism is an important economic sector in Indonesia. Natural and cultural resources are important components of tourism in Indonesia. Banyuwangi is one of the regencies in East Java which is located on the eastern point of Java. This is the largest regency of Java island with total area reaching 5782.50 km2. It attracts tourists to come. Among the factors the charm of its nature and culture. The rich of natural and cultural resources encourages local government to more aggressively promote Banyuwangi as regency eligible to be one of favorite Indonesia tourism destinations. Banyuwangi government has continually promoted the tourism objects and attractions through Department of Culture and Tourism. The study is aimed to examine the implementation of the program. To know the strengths, weaknesses, opportunities and threats of the program. This research used descriptive qualitative method. It involves organizing, accounting for and explaining the data (Cohen et al, 2007: 461). Data collection method in this study include observation, interviews, and documentation. The data were analyzed by using SWOT analysis. SWOT analysis is used to formulate the recommendations in order to produce a model or right strategy for village-based English training. The result of the research have eleven supporting factors and have eight obstacle factors of English training program. In the Tamansari and Bangsring.